A low band gap conjugated small molecule based on isoindigo flanked with diketopyrrolopyrrole for efficient organic solar cells. (February 2017) - Jung, Jae Woong
Abstract: Herein, we report design and synthesis of DPP-Ii-DPP, a conjugated small molecule (SM) composed of central isoindigo flanked with diketopyrrolopyrrole (DPP), for organic solar cell (OSC) application. The DPP-Ii-DPP exhibited broad and intense absorption in 400–800 nm in wavelength with a low optical band gap of 1.46 eV. However, in contrast to common DPP-based SMs with strong electron-donating central moiety, DPP-Ii-DPP exhibited much lowered energy levels (HOMO = −5.56 eV), which is beneficial to achieve high open circuit voltage (VOC ) of the devices. For the purpose to optimize power conversion efficiency (PCE) of OSCs based on DPP-Ii-DPP, the photoactive blend film was treated with thermal/solvent annealing or processing additive. Among which, the device with solvent annealing exhibited an optimized PCE of 5.86% with a VOC of 0.86 V, a JSC of 11.75 mA/cm 2 and FF of 0.58. This work shows the potential of DPP-Ii-DPP as a promising SM-based electron donor materials for efficient OSCs. Highlights: An ovel small molecular electron donor (DPP-Ii-DPP) was designed and synthesized. DPP-Ii-DPP exhibited low band gap (1.46 eV) and low-lying energy levels (HOMO = −5.56 eV). Solvent annealing-treated solar cells based on DPP-Ii-DPP and PC71 BM achieved power conversion efficiency up to 5.86%.